Application of laser-induced incandescence for the determination of primary particle sizes of nanoparticles demonstrated using carbon blacks - Will, Stefan; Leipertz, Alfred; Schraml, Stephan; Dankers, Stefan (Chemical Engineering & Technology, 2002)
Time-resolved laser-induced incandescence (TIRE-LII), which relies on the heating of particles by a laser pulse and subsequent detection of the thermal radiation, has been successfully tested for the particle sizing of nanoscale carbon blacks. For this purpose, different types of commercially available carbon black powders are dispersed in a measurement chamber by means of a dry ultrasonic dispersion. After the sedimentation of big clusters out of the measurement volume reproducible LII-measurements can be performed. A good correlation between primary particle sizes measured by LII and specified product properties, which are provided by transmission electron microscopy (TEM)-analysis, is found. Furthermore, it turns out that the LII results are not affected by the aggregate structure.